2002
DOI: 10.1590/s0100-879x2002001000001
|View full text |Cite
|
Sign up to set email alerts
|

A Portuguese version of the Christo Inventory for Substance-Misuse Services: a simple outcome evaluation tool

Abstract: The Christo Inventory for Substance-Misuse Services (CISS) is a single page outcome evaluation tool completed by drug alcohol service workers either on the basis of direct client interviews or of personal experience of their client supplemented by existing assessment notes. It was developed to assist substance misuse services to empirically demonstrate the effectiveness of their treatments to their respective funding bodies. Its 0 to 20 unidimensional scale consists of 10 items reflecting clients' problems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Another study showed that in CRIAA, one to 12 months in treatment was associated with some improvement in the patient's condition especially in criminal behavior. 10 Motivation towards treatment is more likely to be an adult characteristic. They usually have fewer adverse consequences due to drug use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that in CRIAA, one to 12 months in treatment was associated with some improvement in the patient's condition especially in criminal behavior. 10 Motivation towards treatment is more likely to be an adult characteristic. They usually have fewer adverse consequences due to drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found out that after six months under treatment considerable improvement could be detected in the consumption of illicit substances and criminal involvement. 10 Characteristics of the sample were analyzed by taking the sample as a whole for the study of correlations and then by comparing the two subsets of extreme adherence (good adherence x no adherence). Correlations between variables were performed as pertinent to the study's objectives.…”
Section: Methodsmentioning
confidence: 99%
“…2) Quantificação de Uso de Drogas Psicoativas: as drogas utilizadas até um mês antes da pesquisa, a frequência do uso, a idade de início do uso e a quantidade consumida foram relatadas com o preenchimento do Inventário Christo 14,15 .…”
Section: Instrumentosunclassified